Progress in Gelatin as Biomaterial for Tissue Engineering - Izeia Lukin; Itsasne Erezuma; Lidia Maeso; Jon Zarate; Martin Federico Desimone; Taleb H. Al-Tel; Alireza Dolatshahi-Pirouz; Gorka Orive (MDPI AG, 2022)
Tissue engineering has become a medical alternative in this society with an ever-increasing lifespan. Advances in the areas of technology and biomaterials have facilitated the use of engineered constructs for medical issues. This review discusses on-going concerns and the latest developments in a widely employed biomaterial in the field of tissue engineering: gelatin. Emerging techniques including 3D bioprinting and gelatin functionalization have demonstrated better mimicking of native tissue by reinforcing gelatin-based systems, among others. This breakthrough facilitates, on the one hand, the manufacturing process when it comes to practicality and cost-effectiveness, which plays a key role in the transition towards clinical application. On the other hand, it can be concluded that gelatin could be considered as one of the promising biomaterials in future trends, in which the focus might be on the detection and diagnosis of diseases rather than treatment.